P10 Communication is the root issue: informing the development of cyberbullying interventions. (3rd September 2019) - Dennehy, R; Meaney, S; Cronin, Mary; Arensman, Ella
Abstract : Background: Cyberbullying is an international public health concern. The potential cost to the physical and mental health of young people calls for action to address this issue. Guided by the UK Medical Research Council guidance on complex interventions and the Behaviour Change Wheel, an approach for applying behavioural theory to intervention development, the aim of this study was to conceptualise cyberbullying from the perspective of post-primary school students to inform the development of an intervention to address the issue. Methods: A systematic review and meta-ethnographic synthesis of qualitative studies related to young people's perceptions of cyberbullying was conducted. A young person's advisory group (aged 16) was established to collaborate with researchers in the design and conduct of a qualitative study across four post-primary schools. 11 focus groups (n=64) were conducted with young people aged 14–17. Data was analysed thematically and the findings were interpreted by the advisory group. Results: The advisory group identified key areas requiring intervention: parental knowledge of the cyber world; parental reaction when approached for help; bodily autonomy (with regard to the sharing of nude images); mental health. They identified ' communication ' as the 'root issu e' in tackling these issues: communication between young people and parents; communication among peers; and communication in the delivery of prevention and intervention programmes for young people. Conclusion: This study provides a thorough understanding of cyberbullying from the perspective of young people. The findings will be used to design, implement, and evaluate interventions that are grounded in young people's experience.